The nature of a beneficiary's interest under a Jersey law trust: Kea Investments v Watson in its historical context. Issue 3 (17th February 2022) - Williams, Sam
Abstract: In Kea Investments v Watson [2021] JRC 009, the Royal Court of Jersey considered for the first time whether a beneficiary's interest under a discretionary trust could be the subject of distraint by a judgment creditor. This article places the decision in its historical context and argues that it reflects the inherent difficulty in reconciling a system of property law which in Jersey has its roots in the customary law of Normandy, and the quintessentially English law concept of the trust as transposed to the island.